The Effect of Parity on Neonatal Mortality in Indonesia (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
The neonatal mortality rate in Indonesia is still relatively high (15 per 1,000 live births). The number of children born to a woman (parity) is also still high. The Total Fertility Rate (TFR) is 2.4 per woman. This study aims to determine the effect of parity on neonatal deaths in Indonesia. We used 2017 IDHS data with a cross-sectional design includes 14,827 live births in the 2012-2017 period. Data were analyzed using the multiple logistic regressions method. The results showed that primipara had a statistically insignificant relationship (p-value > 0.05) compared with multipara. While parity≥4 had a risk of 1.90 times experienced on neonatal mortality compared with multipara (95% CI:1,00-3,63) after being controlled by the maternal age, birth attendant, and place of delivery and statistically significant (p-value≤0,05). Thus, parity ≥4 was significantly associated with neonatal mortality. The more children born to mothers, the higher the risk of neonatal death. While parity 1 did not have a significant relationship with neonatal mortality. It is recommended that family planning programs be increased to reduce parity to avoid the risk of neonatal death. The BKKBN program should be improved in reducing TFR.